GABAA receptor α2 subtype activation suppresses retinal spreading depression. (9th July 2015) - Wang, M.; Li, Y.; Lin, Y.
Highlights: Abundant α2, and to a lesser extent, α5 of GABAA receptor are expressed in the chick retina. GABAA receptor α subtype activation suppresses cortical spreading depression in chick retina. GABAA receptor α2 subtype, but not α5, is involved in early stage of migraine. Abstract: Cortical spreading depression (SD) is a transient propagating neuronal excitation followed by depression, which is generally accepted as the underlying cause of migraine. The inhibitory γ-aminobutyric acid type A (GABAA ) receptor activation not only reduces cortical SD frequency and propagation, but also relieves migraine headache. This study aims to determine the role of major α subtypes of GABAA receptor in mediating SD genesis and propagation using an efficient in vitro chick retinal model. We firstly demonstrated that abundant α2, and to a lesser extent, α5 of GABAA receptor expression in the chick retina, enabled the tissue useful for studying GABAA receptor pharmacology and SD. Marked suppression of SD by SL651498 and TPA023 was observed at 10 μmol L −1 and 50 μmol L −1, respectively, suggesting a critical role of GABAA receptor α subtypes, in particular α2, in modulating retinal SD elicitation and propagation. The negative data on NS11394 at 3 μmol L −1 on SD and the little positive selectivity of TPA023 for α5 did not support that α5 subtype is involved in SD genesis and propagation. Our data provide strong evidence that α2, but not α5 is involved in the early stage of migraine, indicating that α2 subtype is a possible drug target related to migraine with aura.